CORPORATE STRATEGY AND REPUTATIONAL IMPACT OF PT PETRINDO JAYA KREASI TBK (CUAN) IN ENTERING THE MSCI INDEX - Muhammad Fathurrahman; May Roni (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2025)
This study explores the corporate strategies of PT Petrindo Jaya Kreasi Tbk (CUAN) in achieving inclusion in the Morgan Stanley Capital International (MSCI) Index, as well as its reputational and strategic impacts on both domestic and foreign investors. The research employs a qualitative approach using a single case study design. Findings indicate that CUAN’s strategies to qualify for MSCI inclusion include increasing free float, strengthening corporate governance and ESG practices, enhancing media exposure and investor communication, and leveraging the reputation of its conglomerate owner, Prajogo Pangestu. Beyond market recognition, CUAN’s inclusion in the MSCI Index signifies a strategic repositioning toward greater corporate transparency and global competitiveness.